Improved Stem Cell MR Detectability in Animal Models by Modification of the Inhalation Gas - Uwe Himmelreich; Ralph Weber; Pedro Ramos-Cabrer; Susanne Wegener; Korinna Kandal; Eric M. Shapiro; Alan P. Koretsky; Mathias Hoehn (Molecular Imaging)
In vivo monitoring of cells labeled with paramagnetic iron oxide particles by magnetic resonance imaging (MRI) is complicated by intrinsic contrast of blood vessels. Distinction between T 2 * effects caused by blood vessels from those caused by labeled cells was so far only possible after carefully following the location of hypointense regions through subsequent slices of T 2 *-weighted 3-D MRI datasets, a procedure that is time consuming and not always reliable in the case of smaller blood vessels. Here, we demonstrate that the modification of the inhalation gas mixture from the routinely used composition 35% O 2 and 65% N 2 O to a mixture containing 95% O 2 and 5% CO 2 results in a contrast suppression of most small blood vessels and reduces the intrinsic T 2 * effect of large vessels dramatically in an animal model. This change in protocol of physiological conditions was well tolerated by all studied animals, even over prolonged experimental times. The changed inhalation gas mixture thus provides a more reliable identification method for small clusters of iron oxide labeled cells in vivo.